On the taxonomy and phylogeny of the skinks Lipinia sekayuensis Grismer, Ismail, Awang, Rizal, & Ahmad and Lipinia surda Boulenger from Peninsular Malaysia - Grismer, L. Lee; Wood, Perry L. Jr.; Syafiq, Muhammad F.; Badli-Sham, Baizul H.; Rizal, Syed A.; Ahmad, Amirrudin B.; Quah, Evan S. H. (Zootaxa, 2016)
An integrative taxonomic analysis based on additional specimens and color photographs of Lipinia sekayuensis and additional color photographs of L. surda from Pulau Tioman and the Gunung Panti Forest Reserve, Peninsular Malaysia confirm the previous hypotheses that L. sekayuensis is a valid species and is the sister species of L. surda. The two species share a 12.8% sequence divergence between them.